Report on the Observance of Standards and Codes, Accounting and Auditing : Revision of the Diagnostic Tool - Summary Note - World Bank (World Bank, Washington, DC, 2017)
The Reports on the Observance of Standards and Codes (ROSC) Accounting and Auditing (A&A) program is a part of the joint World Bank-International Monetary Fund (IMF) initiative on assisting member countries to strengthen their financial system by improving their capacity to comply with important internationally recognized standards and codes. The ROSC A&A diagnostic tool was first developed in 2001. Whilst a number of relatively limited amendments and updates have been introduced over the years, this recent project is the first detailed revision of the tool. The purpose of this note is to provide an overview of the key changes to the diagnostic tool. In revising the diagnostic tool, the Bank pursued two main objectives: (i) update and improve the existing four-part diagnostic tool to allow task teams to assess corporate sector A&A practices in a manner that is consistent and comprehensive; and (ii) develop a set of guidelines to help teams in planning and conducting ROSC A&A assessments using the revised diagnostic tool.